Attack on Titan. 02 - Isayama, Hajime, 1986- (Kodansha Comics, 2012)
"The Colossal Titan has breached humanity's first line of defense, Wall Maria. Mikasa, the 104th Training Corps' ace and Eren's best friend, may be the only one capable of defeating them, but beneath her calm exterior lurks a dark past. When all looks lost a new Titan appears and begins to slaughter its fellow Titans. Could this new monster be a blessing in disguise, or is the truth something much more sinister?"--P. [4] of cover.